Thermodynamic data selection applied to radionuclides and chemotoxic elements: An overview of the ThermoChimie-TDB. (April 2015) - Grivé, Mireia; Duro, Lara; Colàs, Elisenda; Giffaut, Eric
Highlights: ThermoChimie is ANDRA thermodynamic database. ThermoChimie development for radionuclides and chemotoxics is presented. Data selection and validation processes are described. Abstract: The thermodynamic database ThermoChimie is developed to meet the needs of performance assessment of radioactive waste disposals, particularly in the context of the Cigéo project (www.cigéo.com). To this purpose, the selection of thermodynamic data on radionuclides and chemotoxic elements has been subject to special attention. The aim of this publication is to present the methodology used in the selection of data on radiological and chemical pollutants in the disposal context for ThermoChimie. Data on radionuclides have been selected in the range of conditions of interest for the French radioactive waste disposal concepts, under Callovo-Oxfordian and cementitious conditions. Temperatures up to the thermal peak of 90 °C and high ionic strengths likely developed due to the degradation of certain ILW-LL waste packages are considered in the selection of thermodynamic data in ThermoChimie. The validity of the selected data is assessed with regard to experimental laboratory results as well as natural analogue systems. The selection of stability constants of aqueous species and solid compounds of radionuclides is based on literature review, dedicated experimental programs and estimation methods, leading to consistent data sets with associated uncertainties. The ThermoChimie database is presented as an efficient support to performance assessment, with traceable references and uncertainties for each datum. All the data are accessible under the public websitewww.thermochimie-tdb.com .